2012
DOI: 10.1007/s11064-012-0924-9
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Efficacy of Eugenol and Isoeugenol in Acrylamide-Induced Neuropathy in rats: Behavioral and Biochemical evidence

Abstract: The primary objective of this investigation was to assess the neuroprotective efficacy of spice active principles namely Eugenol (Eug) and isoeugenol (IE) in an acrylamide (ACR) neuropathy model in rats. In the present study, ACR administration (50 mg/kg bw, i.p. 3 times/week) for 5 weeks to growing rats caused typical symptoms of neuropathy. We found that treatment of ACR rats with spice active principles (10 mg/kg bw, for 5 weeks) caused marked improvement in gait score and responses in a battery of behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(71 citation statements)
references
References 62 publications
9
62
0
Order By: Relevance
“…The ability of eugenol to directly suppress the enhanced AChE activity following Al intoxication in the current study could be explained with the finding of an in vitro study that demonstrated a potential anti-cholinesterase property of eugenol (51). Similarly, eugenol was found to normalise the cortical AChE level in acrylamide-induced brain neuropathy in rats (21).…”
Section: Figure 3 Effect Of Eugenol And/or Aluminium On Brain Acetylcsupporting
confidence: 60%
See 2 more Smart Citations
“…The ability of eugenol to directly suppress the enhanced AChE activity following Al intoxication in the current study could be explained with the finding of an in vitro study that demonstrated a potential anti-cholinesterase property of eugenol (51). Similarly, eugenol was found to normalise the cortical AChE level in acrylamide-induced brain neuropathy in rats (21).…”
Section: Figure 3 Effect Of Eugenol And/or Aluminium On Brain Acetylcsupporting
confidence: 60%
“…AChE is a significant biological component of the membrane that contributes to its integrity. Induction of the AChE activity causes faster acetylcholine degradation and consequent lowered stimulation of acetylcholine receptors, which produces a reduction of diverse cholinergic (learning and memory), as well as non-cholinergic (cell proliferation and neurite outgrowth) functions (12,21). In the current study, sub-chronic administration of Al induced significantly the brain AChE activity.…”
Section: Figure 3 Effect Of Eugenol And/or Aluminium On Brain Acetylcsupporting
confidence: 45%
See 1 more Smart Citation
“…To test if other xenobiotics are capable of activating wdr-23, we also tested the neurotoxin and suspected carcinogen acrylamide, an electrophile present in cooked food (41) that forms protein adducts (42), elevates reactive oxygen species and lipid peroxidation, depletes glutathione (43,44), and strongly activates SKN-1 target genes in C. elegans (45). As shown in Fig.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Exposure to ACR elevates the generation of reactive oxygen species and induces apoptosis in PC12 cells (9). Also, in rodent models, it has caused lipid peroxidation, depletion in GSH levels, and alterations in apoptotic markers (8,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%